Weight of the left and right ventricle of the heart during fetal life. Issue 6 (June 1972) - Hislop, Alison; Reid, Lynne
Abstract : The hearts from 31 fetuses aged from 12 to 40 weeks' gestation were dissected after fixation. The right ventricle and the left ventricle plus septum were weighed separately and a ratio was established. The total and separate ventricular weights increase steadily with age and at a similar rate. Throughout fetal life the left ventricle plus septum is larger than the right ventricle, but the right ventricle forms a greater proportion of the total ventricular weight than it does in the child or the adult. For the first time, a table of normal fetal heart weights and ratios obtained using the method of Fulton, Hutchinson, and Jones (1952) is presented.